Direct digital control of thyristor networks : an investigation into the on-line control of thyristor networks by means of a small digital computer - Rodd, Michael Godfrey (Department of Electrical Engineering, 2016)
This thesis is an investigation into the applications of a digital computer to the on-line control of thyristor networks. This will involve producing hardware and software to determine firing sequences, firing delays, etc., and to execute the firing instructions. These are to be determined by the computer from the initial instructions and information fed back from the system, correlated with information in the memory. The ultimate aim is geared towards the control of induction motors, based on research work at present being carried out under Professor N.C.Enslin, at the University of Cape Town, on the speed control of induction motors by thyristor networks.